Sukcesja saproksylicznych chrząszczy (Coleoptera) na powierzchniach pohuraganowych w drzewostanach sosnowych Puszczy Piskiej - Gutowski, Jerzy; Kubisz, Daniel; Sućko, Krzysztof; Zub, Karol (Leśne Prace Badawcze, 2010)
The aim of our investigations was to identify the abundance and dynamics of species composition of saproxylic beetles in those Scots pine stands damaged by a windstorm in the Piska Forest in 2002. We compared three plots: (1) a windthrow area without human interference (reference forest ‘Szast’), (2) an area managed after the windstorm, and (3) a control area, not disturbed by the windstorm. During study period (2005–2007) we captured about 24,000 individual Coleoptera, belonging to 659 species, including 322 saproxylic species. Moreover, we discovered 42 species new to the Mazury Lake District. We encountered more species and specimens of Coleoptera in the stands managed after windstorm than in the reference forest ‘Szast’, but this difference was not statistically significant. The lowest number of specimens was found in those stands left undisturbed by the windstorm (control plot). The dominance structure in ‘Szast’ differed slightly from the community structure in managed stands and was completely different from that of the undisturbed forest. The Shannon-Weaver index of species diversity was highest for the stands not affected by the windstorm, substantially lower for the reference forest ‘Szast’, and lowest for managed windthrow stands. The difference between undisturbed forest and windthrow areas was considerably bigger than that between the reference forest ‘Szast’ and managed stands affected by the windstorm. During thee years of study, we recorded distinct changes in the dominance structure of beetles, a decrease of the species diversity index and statistically-significantly fewer species in 2007 than in 2005. Our investigations demonstrated that dead wood left in the forest did not cause an increase in those beetles considered as tree stand pests. Disturbance caused by windstorms positively affected species diversity of beetles in the Scots pine stands. The monitoring of succession in saproxylic beetle communities should be concomitant with the monitoring of dead wood and should be done on more than one reference surface.